Real-time quantitative PCR detection of Mycobacterium avium subspecies in meat products - Klanicova, B; Slaná, Iva; Vondruskova, H; Kaevska, Marija; Pavlík, Ivo (Journal of food protection, 2011)
The aim of this work was to examine various purchased meat products and to find out if any traces of Mycobacterium avium subsp. avium, M. avium subsp. hominissuis, and M. avium subsp. paratuberculosis could be detected in these samples. Analysis of the meat products (raw, cooked, and fermented) was performed using a real-time quantitative PCR (qPCR) method for the detection of specific insertion sequences: duplex qPCR for the detection of IS900 specific for M. avium subsp. paratuberculosis, and triplex qPCR for the detection of IS901 specific for Mycobacterium avium subsp. avium and IS 1245 specific for M. avium subsp. hominissuis. Of the 77 analyzed meat samples, 17 (22%) were found to contain M. avium subsp. paratuberculosis DNA, 4 (5%) samples contained Mycobacterium avium subsp. avium DNA, and in 12 (16%) samples M. avium subsp. hominissuis DNA was detected. The concentration of M. avium subsp. paratuberculosis and M. avium subsp. hominissuis DNA in some meat products exceeded 10(4) genomes per g. Culture examination of these mycobacterial subspecies was negative. By analyzing a range of meat products, we have provided evidence to support the hypothesis that M. avium is present in everyday commodities sold to the general public.
Keywords: Prevalence; Consumer Product Safety; druhová specificita; Meat Products; Polymerase Chain Reaction; polymerázová řetězová reakce; prevalence; kontaminace potravin; DNA bakterií; DNA, Bacterial; lidé; spotřebitelská bezpečnost produktů; Species Specificity; masné výrobky; Mycobacterium avium; Food Contamination; Humans